2005
DOI: 10.1038/sj.ijir.3901312
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of extragenital vascular disease in patients with erectile dysfunction of arterial origin

Abstract: This research was carried out to evaluate the prevalence of carotid and/or lower limb artery abnormalities in patients with arterial erectile dysfunction (ED). To this end, patients with ED (Andrology Unit) or suspected peripheral atherosclerosis (Angiology Unit) underwent an independent and parallel echo-Duplex examination. The Andrology Unit examined 167 patients with ED of different etiologies: 52 of them had penile artery insufficiency and consequently their carotids and lower limb arteries had to be evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…[6][7][8] Recent evidence has clearly shown that penile artery abnormalities in these patients are an ominous sign of the presence of a generalized arterial/arteriolar insufficiency or of atherosclerotic disease in other parts of the body. 3,18 The assumption of ED as a sign of atherosclerosis is also supported by a correlation between retinal vascular disease and low cavernous PSV. 19 Atherosclerotic lesions may progress over decades and their progression in various arterial districts seems to be associated with the presence of cardiovascular risk factors and/or host's response (chronic low-grade inflammation state) to the clinical management (dietetic and pharmacological strategies) of these factors.…”
Section: Discussionmentioning
confidence: 82%
“…[6][7][8] Recent evidence has clearly shown that penile artery abnormalities in these patients are an ominous sign of the presence of a generalized arterial/arteriolar insufficiency or of atherosclerotic disease in other parts of the body. 3,18 The assumption of ED as a sign of atherosclerosis is also supported by a correlation between retinal vascular disease and low cavernous PSV. 19 Atherosclerotic lesions may progress over decades and their progression in various arterial districts seems to be associated with the presence of cardiovascular risk factors and/or host's response (chronic low-grade inflammation state) to the clinical management (dietetic and pharmacological strategies) of these factors.…”
Section: Discussionmentioning
confidence: 82%
“…One study found that penile artery insufficiency is associated with carotid and/or lower limb artery ultrasound abnormalities (atheroma or marked intima-media thickness) approximately 75% of the time. 29 Another study found that the severity of ED based on penile Doppler ultrasound correlates with associated ultrasound abnormalities in the carotid artery, lower limb arteries or both vascular beds. Men with ED and both carotid and lower limb abnormalities had the most severe penile artery disease based on ultrasound assessments of all three vascular beds.…”
Section: Erectile Dysfunction As a Harbinger Of Cvd Kl Billups Et Almentioning
confidence: 99%
“…Psychogenic and somatic erectile dysfunction are equally prevalent in men visiting their general practitioner for sexual dysfunction. In young men, erectile dysfunction is mostly caused by a psychological condition, compared to older men, in whom a somatic cause is more common (19,20).…”
Section: Correlation Between Lower Urinary Tract Symptoms and Erectilmentioning
confidence: 99%